Experimental Study on Permeability and Stress Sensitivity of Different Lithological Surrounding Rock Combinations - Lv, Runsheng; Xue, Jiao; Zhang, Zhen; Ma, Xinyu; Li, Bing; Zhu, Yuchen; Li, Yunbo (Frontiers in Earth Science, 2022)
The different lithological combinations of the surrounding rock of coal seams play a key role in controlling the enrichment and migration of coalbed methane (gas), and their permeability and stress sensitivity have important theoretical guiding significance for the regional election and evaluation of coalbed methane development. In this paper, the HB-2 type coal rock sample pore permeability adsorption simulation measurement device is used to carry out the sensitivity experiment of the permeability of different surrounding rock combinations on the effective stress of the No. 3 coal seam roof in the Daping coal mine area, Luan, Shanxi. The sensitivity coefficient of permeability to effective stress, the maximum damage rate of permeability, and other parameters are defined to characterize the response mode of permeability to effective stress and the dynamic change rule of permeability, and reveal the control mechanism of effective stress on permeability change of different surrounding rock combinations. The results show that the permeability of the roof of No. 3 coal seam is highly sensitive to the effective stress, and the permeability of different surrounding rock combinations decreases with the increase of the effective stress, and there is a strong negative exponential correlation between the permeability and the effective stress; the stress sensitivity coefficients of different surrounding rock combinations under unloading stress are higher than those under loading; the permeability changes of specimens with different combinations of surrounding rock under the same experimental conditions are varied and the differentiation phenomenon is significant; the permeability is affected by lithology, pore fissure degree, and different combinations of surrounding rock, among which different combinations of surrounding rock are the main controlling factors for the dynamic change of permeability.